Ice is-- whee! - Greene, Carol; Sharp, Paul (Chicago : Childrens Press, 1983)
Ice is cold, slippery, pretty, and a lot of fun for children.
"Level B, early fluent"--Cover p. [4].
Includes a word list.
1.
1.3
K-3
P-2.
Keywords: Ice -- Fiction; Ice -- Fiction